Imperceptible reversible watermarking of radiographic images based on quantum noise masking. (July 2018) - Pan, Wei; Bouslimi, Dalel; Karasad, Mohamed; Cozic, Michel; Coatrieux, Gouenou
Highlights: A watermark "psychovisual mask" for radiographic images is proposed. A locally adapted histogram shifting based lossless watermarking is given. Watermark is masked into the image quantum noise to preserve the diagnosis value. Theoretical distortion/capacity performances into image anatomical parts are given. Theoretical results are experimentally verified. Abstract: Background and objective: Advances in information and communication technologies boost the sharing and remote access to medical images. Along with this evolution, needs in terms of data security are also increased. Watermarking can contribute to better protect images by dissimulating into their pixels some security attributes (e.g., digital signature, user identifier). But, to take full advantage of this technology in healthcare, one key problem to address is to ensure that the image distortion induced by the watermarking process does not endanger the image diagnosis value. To overcome this issue, reversible watermarking is one solution. It allows watermark removal with the exact recovery of the image. Unfortunately, reversibility does not mean that imperceptibility constraints are relaxed. Indeed, once the watermark removed, the image is unprotected. It is thus important to ensure the invisibility of reversible watermark in order to ensure a permanent image protection. Methods: We propose a new fragile reversible watermarking scheme for digital radiographic images, the main originality of which stands in masking a reversible watermark into the image quantum noise (the dominant noise in radiographic images). More clearly, in order to ensure the watermark imperceptibility, our scheme differentiates the image black background, where message embedding is conducted into pixel gray values with the well-known histogram shifting (HS) modulation, from the anatomical object, where HS is applied to wavelet detail coefficients, masking the watermark with the image quantum noise. In order to maintain the watermark embedder and reader synchronized in terms of image partitioning and insertion domain, our scheme makes use of different classification processes that are invariant to message embedding. Results: We provide the theoretical performance limits of our scheme into the image quantum noise in terms of image distortion and message size (i.e. capacity). Experiments conducted on more than 800 12 bits radiographic images of different anatomical structures show that our scheme induces a very low image distortion ( PSNR ∼ 76.5  dB ) for a relatively important capacity (capacity∼ 0.02 bits of message per pixel). Conclusions: The proposed watermarking scheme, while being reversible, preserves the diagnosis value of radiographic images by masking the watermark into the quantum noise. As theoretically and experimentally established our scheme offers a good capacity/image quality compromise that can support different watermarking based security services such as integrity and authenticity control. The watermark can be kept into the image during the interpretation of the image, offering thus a continuous protection. Such a masking strategy can be seen as the first psychovisual model for radiographic images. The reversibility allows the watermark update when necessary.